Pretreat immunosuppressants in whole blood without vortexing and centrifugation - Rui Zhang; Ren-Jie Yang; Ping-An Zhang; Shao-Ting Wang (Advances in Sample Preparation, 2025)
Background: Precise measurement of immunosuppressant levels in whole blood is critical for monitoring post-transplant patient outcomes. Conventional protein precipitation (PP) methods, which rely on vortex mixing and centrifugation, present substantial limitations in terms of automation and scalability. To address these challenges, we developed a novel pretreatment strategy termed “Pseudo-Protein-Precipitation combined with Cold-Induced Phase Separation” (PPP+CIPS), designed to simplify sample processing and enhance high-throughput efficiency. Results: The PPP+CIPS method employs 48 % acetonitrile to generate a semi-homogeneous blood suspension, enabling in-situ drug extraction via CIPS. Notably, this approach eliminates the need for vortexing and centrifugation—key bottlenecks in traditional therapeutic drug monitoring workflows. By leveraging 96-well plates and multi-channel pipettes, the protocol reduces pretreatment time to approximately one-third of that required by PP. Clinical validation (n = 288 in total) revealed strong concordance with established methods, with 94 % of tacrolimus, 95 % of cyclosporin A, and 92 % of sirolimus measurements falling within ±20 % agreement limits. Significance: The PPP+CIPS strategy marks a significant leap forward in high-throughput therapeutic drug monitoring for immunosuppressants. Its seamless integration with 96-well formats and static processing workflows makes it a promising cornerstone for future automated and integrated TDM systems.